Koefisien perpindahan massa dan difusivitas efektif pada proses pengeringan dalam kolom fixed bed pada suhu rendah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Drying processes for heat reluctictant, such as pharmaceutical products(vitamin C), needed special handling for example a low temperature drying in order to minimize damage. The principle of drying processes dealt with heat and mass transfer simultaneously so mathematic models can be developed based on the heat and mass balances.These models were solved by numerical method while Kya and de constants can be evaluated with Hooke-Jeeves optimization method. The Experiment of drying processes at the Vitamin C was carried out in a drier set with fixed Bed columm at low temperature.The Operation variables were Reynold number, the ratio of bed thickness and columm diameter, humidity of air and the ratio of air temperature and solid temperature.Correlation of mass tranfer coefisient(Kya) and the axial effective diffusivity(DE) with operation variables can be expressed in sherwood's which is represented by the following emperical equation: sh=4.627.10.Re 0.09069(Z/Dt)0,1242Y0,1614(tg/Ts)0,5454 with an average error of 1.5% Axial effective diffusivity can be represented by the following emperical equation:De/Dab=8,056.10-3Re0,02005(Z/Dt)0,1046Y0,2323.(Tg/Ts)0,2264 with an average error of 1,6% These equation are valid for 15,9